PENGARUH HARI PERDAGANGAN TERHADAP RETURN SAHAM: PENGUJIAN MONDAY, WEEK-FOUR, DAN ROGALSKI EFFECT DI BURSA EFEK INDONESIA - Sarwinda, Sarwinda; Asakdiyah, Salamatun (Universitas Ahmad Dahlan, 2013)
This research is aimed to test the influence of trading days to return its shares at the Indonesian Stock Exchange by using 31 stocks listed on the meantime, the LQ45 during the period of research February 2011-January 2013. Use sampling techniques of sampling purposive with criteria sample is actively traded shares during a period of research. In analyzing the study data used multiple linear regression analysis method with variable dummy. An independent variable in this research is trading days shares in the Indonesia Stock Exchange and the dependent variable, regression equation of which is used to test each hypothesis of this research is to return shares daily. Results of the research indicate that there is an influence of the trading days against the return of shares in Indonesia Stock Exchange. Return lowest is on Monday and highest return on Friday. Return on Friday that negative influenced by return on Monday that negative. The research found the Week-four effect, but research not proved the existence of Rogalski effect in Indonesia Stock Exchange.